Ethics Demonstrated in Geometrical Order, by Baruch Spinoza: Translated and edited by Pedro Lomba - Ocaña Guzmán, Federico (Analysis. Journal of Philosophical Research, 2020)
Review of: B. Spinoza (2020), Ética demostrada según el orden geométrico. Traducción y edición de Pedro Lomba. Madrid: Trotta.